Familial dyskeratotic comedones in a female with positive family history: A rare entity - Anup Kumar Tiwary; Dharmendra Kumar Mishra; Shyam Sundar Chaudhary (Our Dermatology Online, 2017)
Familial dyskeratotic comedones is an inherited disorder with characteristic clinical features characterized by disseminated, hyperkeratotic papules and comedones with evidence of dyskeratosis on histopathology. In the light of unrewarding treatment and rarity of this entity, herein we report this rare disorder in a female patient having positive family history.